Pengaruh Kualitas Dan Harga Produk Terhadap Minat Beli Pelanggan PT.Anugerah Dwi Pratama - Mustika Sari (Jurnal Riset dan Inovasi Manajemen, 2023)
Anugerah Dwi Pratama is a company engaged in the supply of goods and services for boiler machines or steam-powered power plants that was founded in 2010 until now. In connection with the growing national and international competition which resulted in a significant decrease in PT. Anugerah Dwi Pratama, it is necessary to carry out an assessment of the determining variables such as quality, product prices on sustainable buying interest, so that the company can continue to maintain and improve its existence. This research helps companies formulate problems to develop company development strategies.